Tarekat Hizib Nahdlatul Wathan Dan Perannya Dalam Perpolitikan Di Lombok - M. Rohman Ziadi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2018)
Tarekat is a Sufi brotherhood in which it contains and practices sufistic principles. In Sufism,there is a very thick concept, namely zuhud. Zuhud is the emptiness of search, which limits his desire to gain the world. From this it can be seen that the Sufic tradition should be reluctant to desire the world, including politics. However, the Hizib Nahdlatul Wathan as a tarekat appeared to be very active in politics, even the founder and Tarekat murshid Hizib Nahdlatul Wathan became a major driver in politics in Lombok. This is interesting, on the one hand the Hizib Nahdlatul Wathan is a tarekat, but on the other hand it looks very active in the politics of Lombok. Therefore,  the authors are interested in studying  more about the Hizib Nahdlatul Wathan and its role in politics in Lombok. There are two problem formulations in this article, namely; what is the concept of teaching the Hizib Nahdlatul Wathan Order? What is the religious foundation of the Hizib Nahdlatul Wathan Order in its political activities in Lombok? To answer the two formulations of the problem the author uses a literature review and interview research method. In addition, the author also uses two theories to dissect the formulation of the problem, namely the tarekat theory and the tarekat and political theory of Martin van Bruinessen. The tarekat theory the author uses to answer the first problem statement. While the theory of tarekat and politics of Martin van Bruinessen, the author uses it to answer the problem statement number two.